Host-Directed Drug Therapies for Neglected Tropical Diseases Caused by Protozoan Parasites - Varikuti, Sanjay; Jha, Bijay Kumar; Volpedo, Greta; Ryan, Nathan M.; Halsey, Gregory; Hamza, Omar M.; McGwire, Bradford S.; Satoskar, Abhay R. (Frontiers in Microbiology, 2018)
The neglected tropical diseases (NTDs) caused by protozoan parasites are a major global health problem and are responsible for significant morbidity and mortality. Current treatments using anti-parasitic drugs are toxic and prolonged with poor patient compliance. In addition, emergence of drug-resistant parasites is rapidly increasing worldwide. Hence, there is a strong need for safer and better therapeutics for these infections. Host-directed therapy using drugs that target host pathways required for pathogen survival or its clearance is considered as a promising approach for treating infections. This review will give summary of current status and advances of host-targeted therapies for treating NTDs caused by protozoa.